IMPLEMENTASI TOTAL QUALITY MANAGEMENT (TQM) PERSPEKTIF TEORI EDWARD DEMING, JURAN, DAN CROSBY - Husna Nashihin; Nazid Mafaza; M.Okky Haryana; Triana Hermawati (At Turots: Jurnal Pendidikan Islam, 2021)
The study of Total Quality Management (TQM) from the perspective of Edward Deming, Juran's Theory, and Crosby's Theory is very urgently carried out in order to find the theoretical construction of the implementation of Total Quality Management (TQM) in educational institutions. The implementation of Edward Deming's theory can be carried out in the following steps: create a solid goal for the improvement of products and services, stop dependence on mass inspection in the field of education, end the habit of conducting business relations only on a fee basis, improve production and service systems constantly and continuously, and institute modern training methods in the workplace. Institutionalize Leadership. The implementation of Juran's Theory in Total Quality Management (TQM) is carried out in the following three stages, namely quality planning (Quality Planning/QP), quality control (Quality Control/QC), and quality improvement (QI). The implementation of Crosby Theory in Total Quality Management (TQM) is carried out with the following steps; Policy legitimacy, constituency development, resource accumulation, Organizational design and modification, mobilizing resources and action, and monitoring the progress and impact of policy changes.